Age and Gender Differences of Metabolic Factors among the Essential Hypertension Patients at a Tertiary Care Hospital in Dhaka (Journal of Science Foundation, 2016)
Background: Metabolic syndrome is a risk factor for cardiovascular disease. Objectives: The purpose of the present study was to see the association of metabolic syndrome with essential hypertension. Methodology: This cross sectional study was carried out in the OPD of the Department of Cardiology at Shaheed Suhrawardy Medical college Hospital, Dhaka from January 2008 to December 2010. All the All the Metabolic syndrome was defined as abnormal fasting serum level of glucose (? 110 mg/dl or 6.1 mmol/L) with abdominal obesity (waist circumference > 102 cm in men and > 88cm in women), triglycerides (? 150mg/dl), High density lipoprotein cholesterol (< 40 mg/dl in men and < 50 mg/dl in women) and hypertension. Results: . A total of 322 patients were enrolled Among hypertensive patients 31.8% had hyperglycemia, 37.9% had high waist circumference, 69.8% had low HDL cholesterol and 54.3% high triglycerides. As per definition of NCEP-ATP-III, metabolic syndrome had been detected in 17% of male, 37% of female and 27% of total population. Conclusion: Metabolic factors are a common association in hypertensive cases. These patients are at increased risk of coronary and cerebro-vascular disease and require more vigorous prevention. Furthermore in all hypertensive patients metabolic screening is recommended.Journal of Science Foundation 2014;12(2): 34-38DOI: http://dx.doi.org/10.3329/jsf.v12i2.27736